Application of fuzzy logic in order to plan and create software for converting sound to text - Hiwa Hasanzadeh; Jafar Majidpour (Institute of Advanced Engineering and Science, 2020)
The challenge of software in the field of converting sound to text is that some words have different meanings. In these situations, the functions of each one is distinguished by the use of fuzzy logic and division of the working part of the work. In this regard, the words must first be classified according to the specialized discipline. In the second place, the principles of writing should be maintained. In this regard, the points and commands and the alignment of the sentence are all items that should be considered in the software. The next item is the volume and speed of word processing and the lack of restrictions in the number of languages used. But the time problem is very important. In this regard, the use of existing codes and the optimization and remedy of the problems is a suitable method.In this research, some issues including security and maintenance of software proprietary rights, and the speed of converting sound to text and reducing noise and optimal performance of software to convert audio to text based on software method and the principles of fuzzy logic and neural network were investigated. Results showed improvement algorithm Analytical and results outcomes.